Mitral valve disease—current management and future challenges. Issue 10025 (26th March 2016) - Nishimura, Rick A; Vahanian, Alec; Eleid, Mackram F; Mack, Michael J
Summary: The field of mitral valve disease diagnosis and management is rapidly changing. New understanding of disease pathology and progression, with improvements in and increased use of sophisticated imaging modalities, have led to early diagnosis and complex treatment. In primary mitral regurgitation, surgical repair is the standard of care. Treatment of asymptomatic patients with severe mitral regurgitation in valve reference centres, in which successful repair is more than 95% and surgical mortality is less than 1%, should be the expectation for the next 5 years. Transcatheter mitral valve repair with a MitraClip device is also producing good outcomes in patients with primary mitral regurgitation who are at high surgical risk. Findings from clinical trials of MitraClip versus surgery in patients of intermediate surgical risk are expected to be initiated in the next few years. In patients with secondary mitral regurgitation, mainly a disease of the left ventricle, the vision for the next 5 years is not nearly as clear. Outcomes from ongoing clinical trials will greatly inform this field. Use of transcatheter techniques, both repair and replacement, is expected to substantially expand. Mitral annular calcification is an increasing problem in elderly people, causing both mitral stenosis and regurgitation which are difficult to treat. There is anecdotal experience with use of transcatheter valves by either a catheter-based approach or as a hybrid technique with open surgery, which is being studied in early feasibility trials.